Operational stress of police officers: A cross-sectional study in three countries with centralized, hierarchical organization. (25th October 2021) - Kukić, Filip; Streetman, Aspen; Koropanovski, Nenad; Ćopić, Nemanja; Fayyad, Fadi; Gurevich, Konstantin; Zaborova, Victoria; Krikheli, Natella; Dopsaj, Milivoj; Heinrich, Katie M
Abstract: Law enforcement is a stressful occupation with both work-related and social-related stressors. Too much stress can negatively affect behaviours, mental states, and job performance. Centralized police organizations limit officers' individual autonomy, likely increasing stress. This study examined differences in occupational stress in two different European countries and one Middle East country. Participants were 351 male police officers from Serbia ( n  = 130, age 36 ± 8 years), Russia ( n  = 121, age 22 ± 4 years), and Lebanon ( n  = 100, age 36 ± 6 years) who completed the 20-item Operational Police Stress Questionnaire in their own language. Items were averaged and interpreted as low (≤2.0), stress (2.1–3.4), and high stress (≥3.5). Analysis of covariance (ANCOVA) analyses using age as the covariate with Bonferroni post hoc analyses were used. A principal component analysis (PCA) was used to determine stress structure per country. Significant differences were found with lower occupational stress in Russian ( P  < 0.001) and Lebanon ( P  = 0.003) than Serbian officers. PCA factor patterns differed by country, with six found for Russian and Lebanese and three for Serbian officers. More work-related stressors were rated higher for the younger Russian officers, while more social-related stressors were rated higher for the older Serbian officers. Results suggest that it is vital to consider officers' stress sources and overall stress levels.